2009
DOI: 10.1177/1087057109336595
|View full text |Cite
|
Sign up to set email alerts
|

Novel Temperature Activation Cell-Based Assay on Thermo-TRP Ion Channels

Abstract: The precise temperature control of the ABI Prism  7900HT Sequence Detection System designed for detection of fluorescence of a biological sample in real-time PCR assays (TaqMan assays) was used to activate Thermo-TRP ion channels, enabling a novel 384-/96-well plate-based assay. Functional pharmacology was verified against the temperature activation using intracellular calcium fluorescence as a measure of ion channel activity. The assay is applicable to both heterologous expression systems and dorsal root gan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…To functionally characterize the effects of the mammothspecific N647D substitution, we resurrected the AncMammoth and AncGajah TRPV3 genes and measured their temperaturedependent gating in transiently transfected HEK293 cells using Fluo-4 calcium flux assays (Aneiros and Dabrowski, 2009;Reubish et al, 2009). We found that both the AncMammoth and AncGajah TRPV3 proteins were expressed at similar levels (Figure S5I) and that the overall gating dynamics of channels were very similar.…”
Section: Substitutions In Temperature-sensitive Transient Receptor Pomentioning
confidence: 94%
See 1 more Smart Citation
“…To functionally characterize the effects of the mammothspecific N647D substitution, we resurrected the AncMammoth and AncGajah TRPV3 genes and measured their temperaturedependent gating in transiently transfected HEK293 cells using Fluo-4 calcium flux assays (Aneiros and Dabrowski, 2009;Reubish et al, 2009). We found that both the AncMammoth and AncGajah TRPV3 proteins were expressed at similar levels (Figure S5I) and that the overall gating dynamics of channels were very similar.…”
Section: Substitutions In Temperature-sensitive Transient Receptor Pomentioning
confidence: 94%
“…Temperature-dependent calcium influx was assayed using the Fluo-4 NW Calcium Assay Kit (Molecular Probes) and a high-throughout qPCR-based assay (Aneiros and Dabrowski, 2009;Reubish et al, 2009). After an initial 30-min loading at 25 C, the temperature was raised from 15 C to 57 C in 2 C steps, and fluorescence was measured after 2 min at each temperature using a Bio-Rad CFX-96 real-time PCR machine.…”
Section: Trpv3 Function Assaysmentioning
confidence: 99%
“…To functionally characterize the mammoth-specific amino acid substitutions in TRPM8, we resurrected the AncMammoth and AncGajah TRPM8 genes (Fig. 3A) and measured their temperature-dependent activity in transiently transfected HEK293 cells using a Fluo-4 calcium influx assay (Aneiros and Dabrowski, 2009;Reubish et al, 2009). We found that the AncGajah TRPM8 had a similar activation profile as other mammalian TRPM8 proteins, for example, it was activated at ~22°C, had half maximum activities (T50) at ~17°C, and maximal activities (Tmax) at 2°C (Fig.…”
Section: Thermal Desensitization Of Trpm8 In Mammothsmentioning
confidence: 99%
“…48 hr after transfection, cells were harvested by trypsinization, centrifuged, resuspended in Hank's balanced salt solution (HBSS) and HEPES assay buffer containing 2.5 mM probenecid, and transferred to a 96-well plate at 150,000 cells/well in 50 μl assay buffer. Temperature-dependent calcium influx was assayed using the Fluo-4 NW Calcium Assay Kit (Molecular Probes) and a high-throughout qPCR-based assay (Aneiros andDabrowski, 2009, Reubish et al, 2009). After an initial 30-min loading at 37°C, the temperature was lowered from 37°C to 2°C in 5°C steps, and fluorescence was measured after 30 s at each temperature using a Bio-Rad CFX-96 real-time PCR machine.…”
Section: Trpm8 Function Assaysmentioning
confidence: 99%
“…A versatile temperature-dependent assay was reported that relied on the rapid TaqMan temperature control to trigger thermoTRPs activation; results were shown to reliably translate to native rat dorsal root ganglia neurons in either 384 or 96 well formats [197].…”
Section: Targeting the Temperature Sensitivity Of Trpa1 With In Vitromentioning
confidence: 99%